Correlates of prevalent HIV infection among adolescents, young adults, and older adult female sex workers in Ghana: Analysis of data from the Ghana biobehavioral survey - Guure, C.; Dery, S.; Afagbedzi, S.; Maya, T.; da-Costa Vroom, F.B.; Torpey, K. (PLOS ONE, 2023)
Background Human immunodeficiency virus infection remains a high burden among key populations such as female sex workers in the world. We aimed to provide distribution of prevalence and correlates of Human immunodeficiency virus infection among adolescent, young, and older adult FSWs in Ghana. Methods This data was obtained from the biobehavioral survey of female sex workers (2020) in Ghana based on a time location sampling approach for the selection of respondents. A sam pling frame was developed taking into consideration list of venues, days, and time that sex workers operate across all the regions of Ghana. These lists were derived from a sampling universe which was obtained during a mapping exercise. All sex workers aged 16 years and above and eligible on the day of visit participated. Human immunodeficiency virus testing was done based on First Response and Oraquick. To obtain estimates for sex workers, sampling weights were calculated and applied to the dataset. Inferential analyses using Bayesian regression models were applied with interaction effects. Results A total of 5,990 participants completed both the biological and behavioral aspects of the study. The HIV prevalence among female sex workers in Ghana was 4.67% (CI: 4.05%, 5.40%). About 70% of the respondents who tested positive for Human immunodeficiency virus were among the older adults (= >25 years) group. Generally, there was a high preva lence variation across the 16 regions of Ghana, from 0.00% to 8.40%. Respondents’ age was a significant contributor to the prevalence of HIV. Respondents who were forced into having sex had higher odds (38%) of being positive in the combined analysis. Respondents who had comprehensive knowledge of HIV had lower odds (39%) of testing positive. Conclusion The findings suggest a low prevalence of HIV among sex workers in 2020 compared to the 2011 and 2015 biobehavioral survey results but higher than the general population. Specifi cally, older adults have a higher prevalence of HIV. There is generally low level of compre hensive knowledge among sex workers. Interventions geared towards increasing FSW knowledge on risky behavior should be vigorously pursued.
Research Article
Keywords: Human immunodeficiency virus; Ghana; female sex workers